Influenza in Portugal, 2014/2015 season - Pechirra, Pedro (2016)
During 2014/2015 season the influenza activity was high, the epidemic period was observed between week 1/2015 and 8/2015 with a maximum of 148 ILI cases per 105 inhabitants in week 4/2015. The influenza B virus, A(H3) and A(H1)pdm09 co-circulated during the season, although influenza B were dominant throughout the winter, except for weeks 4, 6 and 7/2015 where it was detected in co-dominance with influenza A virus, situation that contrasts with European influenza picture. The antigenic and genetic analysis of circulating influenza A(H3) and B virus showed differences regarding 2014/2015 influenza vaccine strains. 70% of A(H3) viruses belonged to subgroup 3C.2a, antigenically different from vaccine strain. A (H3) positive were recorded in higher percentage in children (0 to 4 years: 40.0% and 5 to 14 years: 39.7%) and in adults over 65 years (36, 8%). A(H1)pdm09 virus were sporadically detected and were similar to the vaccine A/California/7/2009 strain. In general, the detected influenza viruses were similar to those recommended strains for next winter`s vaccine 2015/2016.